PENGARUH PELATIHAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN - Sriwati Sriwati (EQUILIBIRIA, 2017)
This research objective is to find out the impact of training and motivation to performance. Performance functions as a dependent variable on this research. Training and motivation is variable function as independent variable. The sample of this research is included thirtysix permanent worker at back office Awal Bros Hospital Batam, acquired by all worker. Data is collected through questionnaire method and analyzed by Statistical Package for the Social Sciences (SPSS) technique.